2001
DOI: 10.1097/00005082-200107000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis

Abstract: Venous thrombosis involving the deep veins is a major US health problem that affects over 2.5 million people annually. The most serious complication of a deep venous thrombosis (DVT) is pulmonary embolism (PE), which is associated with 50,000 to 200,000 deaths each year. DVT and PE are often silent and difficult to detect by clinical examination; however, DVT rarely occurs in the absence of risk factors. This article reviews normal venous anatomy and discusses the etiology of DVT, its clinical manifestations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Its sequelae include post-thrombotic syndrome and pulmonary embolism, which can result in long-term disability or death [2]. Accurate detection of thrombosis and assessment of its size and distribution are critical for treatment decision-making [36].…”
Section: Introductionmentioning
confidence: 99%
“…Its sequelae include post-thrombotic syndrome and pulmonary embolism, which can result in long-term disability or death [2]. Accurate detection of thrombosis and assessment of its size and distribution are critical for treatment decision-making [36].…”
Section: Introductionmentioning
confidence: 99%
“…Although DVTs and PEs are often silent and difficult to detect by clinical examination, they rarely occur in the absence of risk factors. 5 This knowledge can improve clinical prediction considerably. 12 Thrombosis can occur anywhere in the circulatory system.…”
Section: Pathophysiologymentioning
confidence: 99%
“…2 The most serious complication of a DVT is pulmonary embolism (PE), which is associated with 50,000 to 200,000 deaths each year. 5 Other studies have found PE to carry a 10% fatality rate. 3 Another major complication of acute DVT is the long-term socioeconomic consequences of postthrombotic syndrome.…”
mentioning
confidence: 95%
“…2 The progress of a developing DVT is comparatively obscure clinically and without specificity. DVTs at autopsy were found to be the cause of death in 72% of those who died with various diseases.…”
Section: Introductionmentioning
confidence: 99%